IONIZATION OF FRUCTOSE MOLECULES BY ELECTRON IMPACT - Zavilopulo, A.М.; Remeta, E.Yu. (Reports of the National Academy of Sciences of Ukraine, 2024)
The ionization processes of fructose molecules in interaction with electrons were investigated by mass spectrometric method. The ionization potential and total ionization cross section were measured experimentally for the first time. The energy structures of the D- and L-forms of the fructose molecule were calculated using Hartree-Fock (HF) and density functional theory (DFT) methods. The ionization potential of a molecule was estimated from the total energies of the molecule and its positive ion (adiabatic approximation) and from the binding energy of the HOMO molecular orbital (MO). The single ionization cross sections of the molecule were calculated using the semiclassical Binar-Encaunter-Bethe (BEB) and classical Gryzinsky (Gryz) approximations. The measured relative total cross section was normalized to a near-threshold Gryz-DFT value. The contributions to the Gryz-DFT cross section from the valence MOs HOMO, HOMO-1, and HOMO-2 are evaluated.